Interlayer-directed multilevel trap engineering for enhanced energy storage in PET dielectric films - Liu, Tao; Liu, Jianjun; Liu, Yang; Qian, Jin; Zhai, Jiwei; Zhou, Yao; Zhou, Tao; Yan, Gui Wei; Xu, Di Ming; Tan, Kar Ban; Liu, Wenfeng; Zhou, Di (Elsevier, 2025)
As demands for high-performance capacitors in high-temperature applications such as electrified transport and pulsed power systems grow, polymer dielectrics with both high discharge energy density (Ud) and superior thermal stability are increasingly needed. In this work, we introduce an interlayer-directed multilevel trap engineering approach to create all-organic sandwich-structured polymer composite films through a one-step dip-coating and hot-pressing process. A high-electron-affinity organic semiconductor, 1,4,5,8-naphthalene tetracarboxylic dianhydride (NTCDA, C₁₄H₄O₆), is incorporated into poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)) and coated onto a central poly(ethylene terephthalate) (PET) layer, which is then sandwiched between two outer PET films. The energy band offset between NTCDA and P(VDF-HFP) creates multilevel deep traps, while the interlayer interfaces introduce effective carrier barriers. This synergistic trap-barrier effect significantly suppresses charge transport and leakage current, resulting in enhanced breakdown strength (Eb) (∼ 678.6 MV·m−1) and excellent energy storage performance (ESP) (Ud ≈ 8.2 J·cm−3, efficiency (η) ≈ 94.3 %) at 25 °C. At 125 °C, a high Ud of 6.4 J·cm−3 is retained. This research offers an effective approach to develop polymer dielectrics that combine thermal stability with high efficiency for cutting-edge energy storage uses.